2019
DOI: 10.1002/em.22272
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase kappa counteracts inflammation‐induced mutagenesis in multiple organs of mice

Abstract: In vitro studies indicate that DNA polymerase kappa (Polκ) is able to accurately and efficiently perform DNA synthesis using templates containing various types of DNA damage, including benzo[a]pyrene (BP)‐induced N2‐deoxyguanosine adducts. In this study, we examined sensitivity of inactivated Polk knock‐in (Polk−/−) mice to BP carcinogenicity in the colon by administering an oral dose of BP plus dextran sulfate sodium (DSS), an inflammation causing promoter of carcinogenesis. Although colon cancer was successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 71 publications
(102 reference statements)
0
12
0
Order By: Relevance
“…Mutagenesis induced by BPDE was elevated in catalytically dead (CD) and knockout (KO) pol κ Nalm-6 cells as well as in mouse embryonic stem cells, confirming the catalytic role of pol κ in suppressing mutations by BPDE [6,11,13,16,92,94]. In mice with wild-type ( polk +/+ ) or a catalytically inactive variant ( polk −/− ) of pol κ, mutagenesis induced by B[a]P was found to be insignificant in the colon, although spontaneous mutation frequency increased significantly in polk −/− mice at old age [95,96,97]. Thus, pol κ appears to catalyze TLS across endogenously generated DNA adducts caused by oxidative damage and alkylating agents in an error-free manner.…”
Section: Fidelity and Selectivitymentioning
confidence: 88%
See 1 more Smart Citation
“…Mutagenesis induced by BPDE was elevated in catalytically dead (CD) and knockout (KO) pol κ Nalm-6 cells as well as in mouse embryonic stem cells, confirming the catalytic role of pol κ in suppressing mutations by BPDE [6,11,13,16,92,94]. In mice with wild-type ( polk +/+ ) or a catalytically inactive variant ( polk −/− ) of pol κ, mutagenesis induced by B[a]P was found to be insignificant in the colon, although spontaneous mutation frequency increased significantly in polk −/− mice at old age [95,96,97]. Thus, pol κ appears to catalyze TLS across endogenously generated DNA adducts caused by oxidative damage and alkylating agents in an error-free manner.…”
Section: Fidelity and Selectivitymentioning
confidence: 88%
“…Thus, pol κ appears to catalyze TLS across endogenously generated DNA adducts caused by oxidative damage and alkylating agents in an error-free manner. Hakura et al showed that B[a]P was not carcinogenic in mice when delivered alone [96]. Mice exposed simultaneously to B[a]P and dextran sulfate sodium (DSS), which causes inflammation in the colon, developed tumors.…”
Section: Fidelity and Selectivitymentioning
confidence: 99%
“…Hakura, et al treated pol κ −/− and pol κ +/+ mice with either the mutagen benzo(a)pyrene (BP), DSS, or both. There was no significant difference in the incidence of tumor development between pol κ −/− and pol κ +/+ mice when treated with both BP and DSS, suggesting that pol κ does not function to repress tumorigenesis [95]. However, using a gpt transgene reporter, the authors showed that DSS treatment alone increased mutagenesis in pol κ −/− mice, and not in pol κ +/+ mice, with G > C transversions being the most frequent errors in both the distal colon and lungs of these mice [95].…”
Section: Pol Kmentioning
confidence: 92%
“…There was no significant difference in the incidence of tumor development between pol κ −/− and pol κ +/+ mice when treated with both BP and DSS, suggesting that pol κ does not function to repress tumorigenesis [95]. However, using a gpt transgene reporter, the authors showed that DSS treatment alone increased mutagenesis in pol κ −/− mice, and not in pol κ +/+ mice, with G > C transversions being the most frequent errors in both the distal colon and lungs of these mice [95]. Taken together, pol κ may display lower fidelity during 8oxoG TLS, but the described in vivo study suggests it does play a role in suppressing mutagenesis in an oxidative stress environment.…”
Section: Pol Kmentioning
confidence: 92%
“…This phenomenon is observed in Rev1 deficient mice, which when crossed to skin-cancer prone mice, exhibit inflammatory hyperplasia and an acceleration of skin cancer [113]. Of note, pol κ deficient mice have increased inflammationmediated mutagenesis, and pol ζ deficient cells exhibit chromosomal breaks and increased sensitivity to nitric oxide, a mediator of inflammatory responses [114,115]. Thus, TLS can potentially alleviate inflammation-mediated DNA lesions and help mitigate stress responses [116][117][118].…”
Section: Tls-induced Mutagenesis Vs Rgs In Cancer Developmentmentioning
confidence: 99%